Composite positive electrode active material and preparation method thereof, positive electrode and all-solid-state battery
By forming Ta and La-F claddings on the surface of the ternary positive electrode active material, the problem of cycling performance deterioration of the ternary positive electrode active material in lithium-ion batteries is solved, and the high cycle stability and rate performance of the battery are achieved.
Patent Information
- Application Number
- CN202411737118.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The presence of particle breakage of the ternary positive electrode active material in lithium-ion batteries, positive electrode oxygen release and strong oxidation of Ni4+ leads to an increase in interface side reactions, resulting in a decline in battery circulation performance.
The composite positive electrode active material adopts a core-shell structure, the first cladding layer is composed of Ta, and the second cladding layer is composed of La and F. Through the specific cladding layer thickness and composition combination, high ion conductivity and good lithium ions are formed. Covering for transmission capability.
The lithium ion conduction between the positive electrode and the electrolyte solid-solid interface is improved, the cycling and rate performance of the battery is improved, and the internal resistance of the battery is reduced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium-ion batteries, and more specifically to a composite positive electrode active material and a preparation method thereof, a positive electrode, and an all-solid-state battery. Background Art
[0002] The ternary cathode active material includes three elements, nickel, cobalt, manganese or nickel, cobalt, and aluminum. It is the most promising cathode material for all-solid-state lithium batteries. It has a high energy density and has attracted widespread attention. However, the ternary cathode is often accompanied by particle breakage, cathode oxygen release, and Ni 4+ The strong oxidizing property will cause redox reaction with sulfide or halide electrolytes, resulting in increased interfacial side reactions and degradation of the composite positive electrode cycle performance. Therefore, it is necessary to further optimize and improve the interfacial contact between the positive electrode and the sulfide (halide) electrolyte, promote lithium ion transmission, reduce side reactions, and improve the battery cycle performance. Summary of the invention
[0003] The purpose of the present invention is to provide a composite positive electrode active material and a preparation method thereof, a positive electrode, and an all-solid-state battery.
[0004] The technical solution of the present invention is achieved in this way:
[0005] The first aspect of the present application provides a composite positive electrode active material, the composite positive electrode active material is a core-shell structure, the core material includes a ternary positive electrode active material, and the shell includes a first coating layer and a second coating layer;
[0006] Wherein, the first coating layer is formed on the surface of the ternary positive electrode active material particles;
[0007] The second coating layer is formed on a surface of the first coating layer that is away from the ternary positive electrode active material particles;
[0008] The first cladding layer comprises Ta;
[0009] The second cladding layer includes La and F.
[0010] In some embodiments, the content of Ta in the first coating layer is S, and the contents of La and F in the second coating layer are M and N respectively, then the following is satisfied: 0.6<(N+S) / M<1.2.
[0011] In some embodiments, the ternary cathode active material is LiNi x Co y Mn 1-x-y O2, where x=0.5~1.0, y>0, x+y<1.
[0012] In some embodiments, the thickness of the first coating layer is 5-20 nm.
[0013] In some embodiments, the thickness of the second coating layer is 1 to 15 nm.
[0014] In some embodiments, the thickness of the first cladding layer is greater than the thickness of the second cladding layer.
[0015] In a second aspect, the present application provides a method for preparing the composite positive electrode active material as described above, comprising the following steps:
[0016] S1, mixing a ternary positive electrode active material precursor, a lithium source, and a Ta source, keeping warm, and then calcining to form an intermediate, wherein the intermediate includes a ternary positive electrode active material and a first coating layer formed on the surface of the ternary positive electrode active material;
[0017] S2. The intermediate, La source and LiF are mixed, dissolved in a solvent, stirred under a constant temperature environment, filtered, dried and calcined twice to obtain a composite positive electrode active material.
[0018] In some embodiments, in step S1, the molar ratio of the ternary cathode active material to the Ta source is 1:(0.008-0.05).
[0019] In some embodiments, in step S2, the molar ratio of the intermediate, La source, and LiF is 1:(0.001-0.01):(0.003-0.015).
[0020] In a third aspect, the present application provides a positive electrode, which includes the composite positive electrode active material as described in the first aspect.
[0021] In a fourth aspect, the present application provides an all-solid-state battery, comprising the composite positive electrode active material as described in the first aspect and / or the positive electrode as described in the third aspect.
[0022] Compared with the prior art, the beneficial technical effect of the technical solution of the present application is: a first coating layer containing Ta is formed on the surface of the ternary positive electrode active material. On the one hand, Ta coating can form a coating layer with high ion conductivity on the surface of the ternary positive electrode active material. On the other hand, Ta can react with Ni during the sintering process. 4+ The reaction occurs with the residual lithium on the surface of the ternary positive electrode active material, which is beneficial to the structural stability of the first coating layer, the improvement of the battery capacity, and the improvement of the battery cycle performance.
[0023] The second coating layer contains La and F. On the one hand, it is beneficial to improve the oxidation resistance of the positive electrode active material and the stability of the positive electrode active material at high voltage. On the other hand, the second coating layer also has good lithium ion transmission ability and can improve the lithium ion conduction at the solid-solid interface between the positive electrode and the electrolyte.
[0024] The first coating layer and the second coating layer cooperate with each other so that the composite positive electrode active material has both high ion release rate and ion migration rate as well as good cycle stability and high voltage stability. It can also effectively improve the interface contact between the positive electrode and the solid electrolyte membrane, so that the prepared battery has both good cycle performance and rate performance, and lower battery internal resistance. DETAILED DESCRIPTION
[0025] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above description and any variations thereof are intended to cover non-exclusive inclusions.
[0027] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0028] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.
[0029] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.
[0030] Throughout the present invention, numerical values represent approximate measures or limits of ranges to cover minor deviations from given values as well as embodiments with about the values mentioned and embodiments with the exact values mentioned. Except for the working examples provided at the end of the detailed description, all numerical values of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.
[0031] Additionally, disclosure of ranges includes disclosure of all values within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.
[0032] Ternary cathodes are often accompanied by particle breakage, cathode oxygen release, and Ni 4+ The strong oxidizing property will cause redox reaction with sulfide or halide electrolytes, resulting in increased interfacial side reactions and degradation of the composite positive electrode cycle performance. Therefore, it is necessary to further optimize and improve the interfacial contact between the positive electrode and the sulfide (halide) electrolyte, promote lithium ion transmission, reduce side reactions, and improve the battery cycle performance.
[0033] In order to solve the above problem, the present invention proposes a technical solution.
[0034] In a first aspect, the present application provides a composite positive electrode active material, wherein the composite positive electrode active material is a core-shell structure, wherein the core material comprises a ternary positive electrode active material, and the shell comprises a first coating layer and a second coating layer;
[0035] Wherein, the first coating layer is formed on the surface of the ternary positive electrode active material particles;
[0036] The second coating layer is formed on a surface of the first coating layer that is away from the ternary positive electrode active material particles;
[0037] The first cladding layer comprises Ta;
[0038] The second cladding layer includes La and F.
[0039] A first coating layer containing Ta is formed on the surface of the ternary positive electrode active material. On the one hand, Ta coating can form a coating layer with high ion conductivity on the surface of the ternary positive electrode active material. On the other hand, Ta can react with Ni during the sintering process. 4+ The reaction occurs with the residual lithium on the surface of the ternary positive electrode active material, which is beneficial to the structural stability of the first coating layer, the improvement of the battery capacity, and the improvement of the battery cycle performance.
[0040] The second coating layer contains La and F. On the one hand, it is beneficial to improve the oxidation resistance of the positive electrode active material and the stability of the positive electrode active material at high voltage. On the other hand, the second coating layer also has good lithium ion transmission ability and can improve the lithium ion conduction at the solid-solid interface between the positive electrode and the electrolyte.
[0041] The first coating layer and the second coating layer cooperate with each other so that the composite positive electrode active material has both high ion release rate and ion migration rate as well as good cycle stability and high voltage stability. It can also effectively improve the interface contact between the positive electrode and the solid electrolyte membrane, so that the prepared battery has both good cycle performance and rate performance, and lower battery internal resistance.
[0042] In some embodiments, the content of Ta in the first coating layer is S, and the contents of La and F in the second coating layer are M and N respectively, then the following is satisfied: 0.6<(N+S) / M<1.2.
[0043] Under this condition, the positive electrode has good interfacial ion transport performance, which significantly improves the side reactions of the positive electrode, making the battery have good rate performance and cycle performance.
[0044] In some embodiments, the ternary cathode active material is LiNi x Co y Mn 1-x-y O2, where x = 0.5 ~ 1.0, y > 0, x + y < 1. This setting is beneficial to improve the energy density of the battery. 4+ The reaction forms a stable structure.
[0045] In some embodiments, the thickness of the first cladding layer is 5-20 nm.
[0046] In specific applications, the specific thickness of the first coating layer may be 7nm, 9nm, 12nm, 15nm, 18nm, etc. or any value within the range, in addition to the end points of the range of 5nm and 20nm. The present invention does not impose any limitation on this.
[0047] In some embodiments, the second cladding layer has a thickness of 1 to 15 nm.
[0048] In specific applications, the specific thickness of the first coating layer may be 1 nm and 15 nm at the end points of the range, or may be 3 nm, 5 nm, 7 nm, 9 nm, 12 nm, 14 nm, etc. or any value within the range. The present invention does not impose any limitation on this.
[0049] In some embodiments, the thickness of the first cladding layer is greater than the thickness of the second cladding layer.
[0050] Ta coating can form a coating layer with high ion conductivity on the surface of the ternary positive electrode active material. The thickness of the first coating layer is greater than the thickness of the second coating layer, which is beneficial to improving the lithium ion transmission rate of the composite positive electrode active material and improving the battery rate performance.
[0051] In a second aspect, the present application provides a method for preparing the composite positive electrode active material as above, comprising the following steps:
[0052] S1, mixing a ternary positive electrode active material precursor, a lithium source, and a Ta source, keeping warm, and then calcining to form an intermediate, wherein the intermediate includes the ternary positive electrode active material and a first coating layer formed on the surface of the ternary positive electrode active material;
[0053] S2. After mixing the intermediate, La source and LiF, dissolving them in a solvent, stirring them under a constant temperature environment, filtering, drying and calcining them twice to obtain a composite positive electrode active material.
[0054] In some embodiments, in step S1, the molar ratio of the ternary positive electrode active material to the Ta source is 1:(0.008-0.05).
[0055] In some embodiments, in step S1, the heat preservation includes the steps of: heat preservation at 400-500°C for 4-6 hours.
[0056] In some embodiments, in step S1, the calcination comprises the steps of: calcining at a calcination temperature of 700-800° C. for 7-10 hours in an air atmosphere.
[0057] In some embodiments, step S1 further includes screening and iron removal. After screening, the particle size D50 of the intermediate is 3-12 μm.
[0058] In some embodiments, in step S2, the molar ratio of the intermediate, the La source, and LiF is 1:(0.001-0.01):(0.003-0.015).
[0059] In some embodiments, in step S2, the solvent is anhydrous ethanol.
[0060] In some embodiments, in step S2, the constant temperature of the constant temperature environment is 30-60°C.
[0061] In some embodiments, in step S2, the stirring time is greater than 4 hours.
[0062] In some preferred embodiments, in step S2, the stirring time is 4 to 20 hours.
[0063] In some embodiments, in step S2, the stirring speed is 300-800 rpm.
[0064] In some embodiments, in step S2, the secondary calcination comprises calcining at a calcination temperature of 300-600° C. for 3-5 hours in an air atmosphere.
[0065] In a third aspect, the present application provides a positive electrode, which includes the composite positive electrode active material as described in the first aspect.
[0066] In some embodiments, the positive electrode includes a positive electrode material layer, and the positive electrode material layer includes the composite positive electrode active material disclosed in the first aspect of the present invention.
[0067] In some embodiments, the positive electrode material layer further includes a binder, which improves the bonding between the composite positive electrode active material particles and also improves the bonding between the positive electrode material layer and the positive electrode current collector.
[0068] In some embodiments, non-limiting examples of binders include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.
[0069] In some embodiments, the cathode material layer includes a conductive agent to impart conductivity to the electrode. The conductive agent may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0070] In some embodiments, the positive electrode sheet includes a positive electrode current collector. Exemplarily, the positive electrode current collector may be aluminum (Al), but is not limited thereto.
[0071] In some embodiments, based on the total mass of the positive electrode material layer, the mass percentage of the composite positive electrode active material particles in the positive electrode material layer is 80%-99%.
[0072] In some embodiments, the mass of the conductive agent accounts for 1%-20% of the mass of the positive electrode material layer.
[0073] In some embodiments, the mass of the binder accounts for 1%-20% of the mass of the positive electrode material layer.
[0074] In some embodiments, the positive electrode plate provided by the present invention further includes solid electrolyte powder for improving the ionic conductivity of the composite positive electrode. The present invention does not limit the type of solid electrolyte powder, which may be oxide solid electrolyte powder, sulfide solid electrolyte powder, or halide solid electrolyte powder. Optionally, the mass of the solid electrolyte powder accounts for 1%-20% of the mass of the positive electrode plate; preferably 5%-20%.
[0075] In some embodiments, the thickness of the positive electrode material layer in the positive electrode plate provided by the present invention is 30-400 μm, for example, 30 μm, 40 μm, 50 μm, 80 μm, 110 μm, 200 μm, 300 μm, 400 μm, preferably 50-110 μm.
[0076] In a fourth aspect, the present application provides an all-solid-state battery, comprising the composite positive electrode active material as in the first aspect and / or the positive electrode as in the third aspect.
[0077] The all-solid-state battery also includes a negative electrode, which includes a negative electrode plate.
[0078] Negative electrode:
[0079] In some embodiments, the negative electrode sheet includes a current collector and a negative active material layer disposed on the current collector.
[0080] In the present invention, the specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. Specifically, the negative electrode active material is selected from natural graphite, artificial graphite, mesophase microcarbon beads (MCMB for short), hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy. Non-limiting examples of carbon materials include crystalline carbon, amorphous carbon and mixtures thereof. Crystalline carbon can be amorphous or flake-shaped, platelet-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.
[0081] In some embodiments, metal elements and metal compounds can also be selected as negative electrode active materials, such as compounds containing metals or metalloids such as Li, Ag, Al, Bi, Cu, Ga, Ge, In, Ni, Pb, Sb, Si, Sn, Sr, and Zn.
[0082] In some embodiments, the mass percentage of the negative electrode active material contained in the negative electrode active material layer may be 80%-99%, for example, 80%, 85%, 90%, 95%, 97%, 99%, etc., preferably 95%-97%.
[0083] In some embodiments, the negative electrode material layer may include a binder; the binder improves the bonding between negative electrode active material particles and the bonding between the negative electrode active material and the current collector.
[0084] In some embodiments, non-limiting examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.
[0085] In some embodiments, the negative electrode active material layer can be obtained by coating a negative electrode slurry on a negative electrode current collector and then drying the negative electrode slurry, wherein the negative electrode slurry includes at least a negative electrode active material and a negative electrode binder. When an aqueous solvent is used as a liquid medium for forming the negative electrode slurry, a thickener is preferably used for slurrying, and the thickener can generally be used to adjust the viscosity of the slurry.
[0086] In some embodiments, the aforementioned viscosity enhancer may be one or more of the following: carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof.
[0087] In some embodiments, the mass proportion of the thickener in the negative electrode slurry can be 0.1%-5%, for example, 0.1%, 0.2%, 0.5%, 0.6%, 1%, 2%, 3%, 4%, 5%, etc., preferably 0.5%-3%, and more preferably 0.6%-2%.
[0088] In some embodiments, the negative electrode active material layer includes a conductive material so that the electrode has conductivity. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., such as copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0089] In some embodiments, the negative electrode current collector can be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0090] All-solid-state batteries also include a solid electrolyte membrane.
[0091] The solid electrolyte membrane includes a solid electrolyte.
[0092] In some embodiments, the solid electrolyte may also be a sulfide solid electrolyte, and the sulfide solid electrolyte includes Li2S-P2S5, Li2S-P2S5-MSx (wherein M is Si, Ge and Sn and 0≤x≤2), Li3.4Si0.4P0.6S4, Li10GeP2S11.7O0.3, Li9.6P3S12, Li7P3S11, Li9P3S9O3, Li10.35Si1 .35P1.65S12、Li9.81Sn0.81P2.19S12、Li10(Si0.5Ge0.5)P2S12、Li(Ge0.5Sn0.5)P2S12、Li(Si0.5Sn0.5)PsS12、Li10GeP2S12(LGPS)、Li6PS5X(wherein X is Cl, Br or I)、Li7P2S8I、Li10.35Ge1.35P1.6 5S12, Li3.25Ge0.25P0.75S4, Li10SnP2S12, Li10SiP2S12 or Li9.54Si1.74P1.44S11.7Cl0.3, or a combination of at least two thereof, a typical but non-limiting combination includes a combination of Li2S-P2S5 and Li2S-P2S5-MSx (wherein M is Si, Ge and Sn and 0≤x≤2), Li3.4Si0. The combination of 4P0.6S4 and Li10GeP2S11.7O0.3, the combination of Li7P3S11, Li9P3S9O3 and Li10.35Si1.35P1.65S12, or the combination of Li9.81Sn0.81P2.19S12, Li10(Si0.5Ge0.5)P2S12, Li(Ge0.5Sn0.5)P2S12 and Li(Si0.5Sn0.5)PsS12.
[0093] In some embodiments, the solid electrolyte may also be a halide solid electrolyte, the general formula of which is Li x MX y N z , wherein 1≤x≤4, 4≤y+nz≤8, and n is the absolute value of the valence of N. The metal element M includes at least one of V, Cr, Mn, Zn, Cd, Fe, Pb, In, Y, Al, Sc, La, Lu, Ga, Zr, or Hf. X includes at least one of the halogen elements F, Cl, Br, and I. N is at least one of the non-metallic elements O and S. Exemplarily, the halide solid electrolyte includes Li3InBr 6-m Clm (0≤m≤6), LiInX4, Li3YX6, Li3ErX6, Li3ScX6, Li3LaX6, Li 3-m Er 1- m Zr m Cl6(x≤0.6), Li 3-m Y 1-m Zr m Cl6(m≤0.6), Li3Y 1-m In m Cl6(0 <m<1)、Li2ZrX6、Li2ZrX y Oz(0<z≤1,y+z=6)、Li2ZrX y A mixture of one or more of Sz (0<z≤1, y+z=6).
[0094] In some preferred embodiments, the halide solid electrolyte includes Li2ZrCl6, Li2ZrCl5F, Li2ZrCl 5.5 O 0.25 、Li3InCl6、Li3YCl6、Li2H f Cl6、LiInBr 4、 At least one of Li3InBr6, Li3LaI6, Li3LuCl6.
[0095] The solid electrolyte includes at least one of a sulfide solid electrolyte and a halide solid electrolyte, and in addition, may also include an oxide solid electrolyte.
[0096] In some embodiments, the oxide solid electrolyte includes any one of garnet ceramics, LISICON-type oxides, NASICON-type oxides, or perovskite-type ceramics, or a combination of at least two of them. Typical but non-limiting combinations include a combination of garnet ceramics and LISICON-type oxides, a combination of LISICON-type oxides and NASICON-type oxides, or a combination of LISICON-type oxides, NASICON-type oxides, and perovskite-type ceramics.
[0097] In some embodiments, the garnet ceramic includes Li 6.5 Ln3Z 1.75 Te 0.25 O 12 、Li7La3Zr2O 12 , Li 6.2 Ga 0.3 La 2.95 R 0.05 Zr2O 12 , Li 6.85 La2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 、Li 6.25 Al 0.25 La3Zr2O 12 、Li 6.75 La3Zr 1.75 Nb 0.25 O 12 or any combination of any one or at least two of Li6.75La3Zr1.75Nb0.25O12. Typical but non-limiting combinations include the combination of Li6.5La3Zr1.75Te0.25O12 and Li7La3Zr2O12, the combination of Li6.85La2.9Ca0.1Zr1.75Nb0.25O12 and Li6.25Al0.25La3Zr2O12, or the combination of Li6.25Al0.25La3Zr2O12, Li6.75La3Zr1.75Nb0.25O12 and Li6.75La3Zr1.75Nb0.25O12.
[0098] In some embodiments, the LISICON-type oxide includes any combination of any one or at least two of Li14Zn(GeO4)4, Li3+x(P1-xSix)O4 (where 0 < x < 1), or Li3+xGexV1-xO4 (where 0 < x < 1). Typical but non-limiting combinations include the combination of Li14Zn(GeO4)4 and Li3+x(P1-xSix)O4 (where 0 < x < 1), the combination of Li3+x(P1-xSix)O4 (where 0 < x < 1) and Li3+xGexV1-xO4 (where 0 < x < 1), or the combination of Li14Zn(GeO4)4, Li3+x(P1-xSix)O4 (where 0 < x < 1) and Li3+xGexV1-xO4 (where 0 < x < 1).
[0099] In some embodiments, the NASICON-type oxide can be defined by LiMM′(PO4)3, where M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr, and La. For example, in certain variants, the NASICON-type oxide can be selected from any one or at least two combinations of Li1+xAlxGe2-x(PO4)3 (LAGP) (where 0 ≤ x ≤ 2), Li1+xAlxTi2-x(PO4)3 (LATP) (where 0 ≤ x ≤ 2), Li1+xYxZr2-x(PO4)3 (LYZP) (where 0 ≤ x ≤ 2), Li1.3Al0.3Ti1.7(PO4)3, LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, LiHf2(PO4)3. Typical but non-limiting combinations include the combination of LAGP and LATP, the combination of LYZP and Li1.3Al0.3Ti1.7(PO4)3, or the combination of LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, and LiHf2(PO4)3.
[0100] In some embodiments, the perovskite-type ceramic includes any one or at least two combinations of Li3.3La0.53TiO3, LiSr1.65Zr1.3Ta1.7O9, Li2x-ySr1-xTayZr1-yO3 (where x = 0.75y and 0.60 < y < 0.75), Li3 / 8Sr7 / 16Nb3 / 4Zr1 / 4O3, Li3xLa(2 / 3-x)TiO3 (where 0 < x < 0.25). Typical but non-limiting combinations include the combination of Li3.3La0.53TiO3 and LiSr1.65Zr1.3Ta1.7O9, the combination of Li2x-ySr1-xTayZr1-yO3 (where x = 0.75y and 0.60 < y < 0.75) and Li3 / 8Sr7 / 16Nb3 / 4Zr1 / 4O3, or the combination of Li3.3La0.53TiO3, LiSr1.65Zr1.3Ta1.7O9, and Li3 / 8Sr7 / 16Nb3 / 4Zr1 / 4O3.
[0101] The preparation method of the present invention will be described below according to the technical content of the present invention, but should not be limited to the following embodiments:
[0102] Example 1
[0103] Preparation of the composite cathode active material:
[0104] S1. Put Ni 0.9 Co 0.05 Mn 0.05The (OH)2 precursor is mixed with the lithium source LiOH and tantalum ethoxide in a high-speed mixer at a molar ratio of 1:1.03:0.03, and then kept at 450°C for 5 hours, heated to 725°C at a heating rate of 3°C / min, and calcined at 725°C in an air atmosphere for 8 hours to obtain an intermediate. After sieving and iron removal, an intermediate with a particle size of D50=9 μm is obtained. The intermediate includes the ternary positive electrode active material LiNi 0.9 Co 0.05 Mn 0.05 O2 and a first coating layer formed on the surface of the ternary positive electrode active material;
[0105] The thickness of the first cladding layer is 10 nm, and the Ta content S in the first cladding layer is 0.27%.
[0106] S2, dissolving the intermediate, nano-La2O3 and LiF in anhydrous ethanol solution at a mass ratio of 1:0.005:0.01, keeping the temperature at 50°C and mechanically stirring at 500 rpm for 5 hours in a glove box, finally filtering, drying, and calcining at 350°C in an air atmosphere for 4 hours to obtain a composite positive electrode active material;
[0107] The thickness of the second coating layer is 8 nm; in the second coating layer, the La content M is 0.48%, and the F content N is 0.27%.
[0108] Among them, (S+N) / M=1.125.
[0109] Example 2
[0110] Preparation of composite positive electrode active materials:
[0111] S1. Ni 0.9 Co 0.05 Mn 0.05 The (OH)2 precursor is mixed with the lithium source LiOH and tantalum ethoxide in a high-speed mixer at a molar ratio of 1:1.03:0.02, and then kept at 450°C for 5 hours, heated to 725°C at a heating rate of 3°C / min, and calcined at 725°C in an air atmosphere for 8 hours to obtain an intermediate. After sieving and iron removal, an intermediate with a particle size of D50=9 μm is obtained. The intermediate includes the ternary positive electrode active material LiNi 0.9 Co 0.05 Mn 0.05 O2 and a first coating layer formed on the surface of the ternary positive electrode active material;
[0112] The thickness of the first coating layer is 8 nm, and the Ta content in the first coating layer is 0.21%;
[0113] S2, dissolving the intermediate, nano-La2O3 and LiF in anhydrous ethanol solution according to a mass ratio of 1:0.006:0.008, keeping the temperature at 50°C and mechanically stirring at 500 rpm for 5 hours in a glove box, finally filtering, drying, and calcining at 350°C in an air atmosphere for 4 hours to obtain a composite positive electrode active material;
[0114] The thickness of the second coating layer is 6 nm; in the second coating layer, the La content M is 0.51%, and the F content N is 0.25%.
[0115] Among them, (S+N) / M=0.9.
[0116] Example 3
[0117] Preparation of composite positive electrode active materials:
[0118] S1. Ni 0.9 Co 0.05 Mn 0.05 The (OH)2 precursor is mixed with the lithium source LiOH and tantalum ethoxide in a high-speed mixer at a molar ratio of 1:1.03:0.015, and then kept at 450°C for 5 hours, heated to 725°C at a heating rate of 3°C / min, and calcined at 725°C in an air atmosphere for 8 hours to obtain an intermediate. After sieving and iron removal, an intermediate with a particle size of D50=9 μm is obtained. The intermediate includes the ternary positive electrode active material LiNi 0.9 Co 0.05 Mn 0.05 O2 and a first coating layer formed on the surface of the ternary positive electrode active material;
[0119] The thickness of the first cladding layer is 7 nm, and the Ta content S in the first cladding layer is 0.14%.
[0120] S2, dissolving the intermediate, nano-La2O3 and LiF in anhydrous ethanol solution according to a mass ratio of 1:0.007:0.006, keeping the temperature at 50°C and mechanically stirring at 500 rpm for 5 hours in a glove box, finally filtering, drying, and calcining at 350°C in an air atmosphere for 4 hours to obtain a composite positive electrode active material;
[0121] The thickness of the second coating layer is 4 nm; in the second coating layer, the La content M is 0.55%, and the F content N is 0.21%.
[0122] Among them, (S+N) / M=0.64.
[0123] Example 4
[0124] Preparation of composite positive electrode active materials:
[0125] S1. Ni 0.9 Co 0.05 Mn0.05 The (OH)2 precursor is mixed with the lithium source LiOH and tantalum ethoxide in a high-speed mixer at a molar ratio of 1:1.03:0.008, and then kept at 450°C for 5 hours, heated to 725°C at a heating rate of 3°C / min, and calcined at 725°C in an air atmosphere for 8 hours to obtain an intermediate. After sieving and iron removal, an intermediate with a particle size of D50=9 μm is obtained. The intermediate includes the ternary positive electrode active material LiNi 0.9 Co 0.05 Mn 0.05 O2 and a first coating layer formed on the surface of the ternary positive electrode active material;
[0126] The thickness of the first cladding layer is 5 nm, and the Ta content S in the first cladding layer is 0.05%.
[0127] S2, dissolving the intermediate, nano-La2O3 and LiF in anhydrous ethanol solution according to a mass ratio of 1:0.007:0.006, keeping the temperature at 50°C and mechanically stirring at 500 rpm for 5 hours in a glove box, finally filtering, drying, and calcining at 350°C in an air atmosphere for 4 hours to obtain a composite positive electrode active material;
[0128] The thickness of the second coating layer is 4 nm; in the second coating layer, the La content M is 0.55%, and the F content N is 0.21%.
[0129] Among them, (S+N) / M=0.47.
[0130] Example 5
[0131] Preparation of composite positive electrode active materials:
[0132] S1. Ni 0.9 Co 0.05 Mn 0.05 The (OH)2 precursor is mixed with the lithium source LiOH and tantalum ethoxide in a high-speed mixer at a molar ratio of 1:1.03:0.05, and then kept at 450°C for 5 hours, heated to 725°C at a heating rate of 3°C / min, and calcined at 725°C in an air atmosphere for 8 hours to obtain an intermediate. After sieving and iron removal, an intermediate with a particle size of D50=9 μm is obtained. The intermediate includes the ternary positive electrode active material LiNi 0.9 Co 0.05 Mn 0.05 O2 and a first coating layer formed on the surface of the ternary positive electrode active material;
[0133] The thickness of the first cladding layer is 14 nm, and the Ta content S in the first cladding layer is 0.35%.
[0134] S2, dissolving the intermediate, nano-La2O3 and LiF in anhydrous ethanol solution at a mass ratio of 1:0.001:0.008, keeping the temperature at 50°C and mechanically stirring at 500 rpm for 5 hours in a glove box, finally filtering, drying, and calcining at 350°C in an air atmosphere for 4 hours to obtain a composite positive electrode active material;
[0135] The thickness of the second coating layer is 1 nm; in the second coating layer, the La content M is 0.35%, and the F content N is 0.25%.
[0136] Among them, (S+N) / M=1.71.
[0137] Comparative Example 1
[0138] Compared with Example 1, the distinguishing technical feature of Comparative Example 1 is that the composite positive electrode active material only includes the ternary positive electrode active material and the second coating layer.
[0139] Comparative Example 2
[0140] Compared with Example 1, the distinguishing technical feature of Comparative Example 2 is that the composite positive electrode active material only includes the ternary positive electrode active material and the first coating layer.
[0141] Comparative Example 3
[0142] Compared with Example 1, the distinguishing technical feature of Comparative Example 3 is that the composite positive electrode active material only includes a ternary positive electrode active material.
[0143] Examples 1 to 5 and Comparative Examples 1 to 3 also include preparing a battery.
[0144] 1. Preparation of positive electrode
[0145] ① Preparation of positive electrode: the composite positive electrode active material, PTFE, super-P, and sulfide solid electrolyte Li6PS5Cl are mixed uniformly according to a mass ratio of 70:3:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a first mixed material, and the first mixed material is rolled to form a first positive electrode layer; the rolling temperature is 60°C, and the rolling time is 5 minutes;
[0146] ② Preparation of negative electrode: Ag-C alloy is used for negative electrode;
[0147] ③ Preparation of solid electrolyte membrane: The sulfide solid electrolyte Li6PS5Cl and the binder PTFE are mixed in a mass ratio of 65:35 and then pressed into a membrane;
[0148] ④Battery structure preparation
[0149] The positive electrode current collector, positive electrode layer, solid electrolyte membrane and negative electrode layer are stacked and hot pressed to obtain a battery structure.
[0150] Performance Test:
[0151] 1. Cycle capacity retention rate:
[0152] At a temperature of 45°C, charge at a current of 0.1C to a charging cut-off voltage of 4.25V, switch to constant voltage charging to a cut-off current of 0.05C, let stand for 0.5h, discharge at a current of 0.1C to a cut-off voltage of 2.5V, let stand for 0.5h, enter the next charge and discharge cycle, and so on, for a total of 100 charge and discharge cycles.
[0153] 2. First discharge capacity test:
[0154] The battery was discharged at a constant current of 0.1C to a cut-off voltage of 2.5V.
[0155] 3. Rate performance test:
[0156] At room temperature (25°C), the fully charged battery is discharged at a current of 0.1C to a cut-off voltage of 2.5V. The capacity obtained by the test is C0.
[0157] At room temperature (25°C), a fully charged battery is discharged at a current of 3C to a cut-off voltage of 2.5V. The capacity obtained by the test is C1, and C1 / C0 is the 3C discharge capacity retention rate below.
[0158] 4. Determination of Ta element content: The Ta element content of the first coating layer is obtained by XPS etching time of 60-120s. After background subtraction of the XPS peak, the peak area is calculated to obtain the Ta atomic ratio, and the content is recorded as mass percentage S%.
[0159] 5. Determination of La and F element content: The La and F element content of the second coating layer is obtained by XPS etching time 0-10S. After background subtraction of the XPS peak, the peak area is calculated to obtain the La and F atomic ratios, and the contents are recorded as mass percentages M% and N%, respectively.
[0160] The relevant test data are as follows:
[0161]
[0162] By comparing Example 1 and Comparative Examples 1, 2, and 3, it can be seen that the first coating layer and the second coating layer cooperate with each other so that the composite positive electrode active material has both high ion release rate and ion migration rate as well as good cycle stability and high voltage stability, and can also effectively improve the interface contact between the positive electrode and the solid electrolyte membrane, so that the prepared battery has both good cycle performance and rate performance.
[0163] By comparing Example 1 with Examples 4 and 5, it can be seen that when 0.6<(N+S) / M<1.2 is satisfied, the battery has good rate performance and cycle performance.
[0164] Although the present invention has described its technical scheme and embodiments in detail, for lithium-ion battery manufacturers and technicians in the same field, they can be inspired by it to select or change the technical features to replace them and obtain a technical scheme that is essentially the same as the present invention. The lithium batteries manufactured thereby should fall within the scope of protection of the present invention.
Claims
1. A composite positive electrode active material, characterized in that: The composite positive electrode active material is a core-shell structure, the core material includes a ternary positive electrode active material, and the shell includes a first coating layer and a second coating layer; Wherein, the first coating layer is formed on the surface of the ternary positive electrode active material particles; The second coating layer is formed on a surface of the first coating layer that is away from the ternary positive electrode active material particles; The first cladding layer comprises Ta; The second cladding layer includes La and F.
2. The composite positive electrode active material according to claim 1, characterized in that: The content of Ta in the first coating layer is S, and the contents of La and F in the second coating layer are M and N respectively, then the following is satisfied: 0.6<(N+S) / M<1.
2.
3. The composite positive electrode active material according to claim 1, characterized in that: The ternary positive electrode active material is LiNi x Co y Mn 1-x-y O2, where x=0.5~1.0, y>0, x+y<1.
4. The composite positive electrode active material according to claim 4, characterized in that: The thickness of the first coating layer is 5-20 nm.
5. The composite positive electrode active material according to claim 4, characterized in that: The thickness of the second coating layer is 1-15 nm.
6. The composite positive electrode active material according to claim 1, characterized in that: The thickness of the first cladding layer is greater than the thickness of the second cladding layer.
7. The method for preparing a composite positive electrode active material according to claim 1, characterized in that: The steps include: S1, mixing a ternary positive electrode active material precursor, a lithium source, and a Ta source, keeping warm, and then calcining to form an intermediate, wherein the intermediate includes a ternary positive electrode active material and a first coating layer formed on the surface of the ternary positive electrode active material; S2. The intermediate, La source and LiF are mixed, dissolved in a solvent, stirred under a constant temperature environment, filtered, dried and calcined twice to obtain a composite positive electrode active material.
8. The preparation method according to claim 7, characterized in that: In the step S1, the molar ratio of the ternary positive electrode active material to the Ta source is 1:(0.008-0.05); and / or, In the step S2, the molar ratio of the intermediate, the La source, and LiF is 1:(0.001-0.01):(0.003-0.015).
9. A positive electrode, characterized in that The positive electrode comprises the composite positive electrode active material as claimed in claim 1.
10. All-solid-state battery, characterized in that: The all-solid-state battery comprises the composite positive electrode active material as claimed in claim 1 and / or the positive electrode as claimed in claim 9.
Citation Information
Patent Citations
Anode active substance and its preparing method and anode and battery
CN101154726A
Modified lithium ion battery cathode material, preparation method thereof, and electrochemical energy saving apparatus using same
CN107516731A
Double-layer coated positive electrode composite material as well as preparation method and application thereof
CN114824227A
Flexible interface coated positive electrode material and solid-state battery
CN114899372A
Ternary positive electrode material, preparation method therefor, and secondary battery
WO2024178920A1